2019
DOI: 10.3390/en12142783
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Emission Evaluation Based on Multi-Objective Balance of Sewing Assembly Line in Apparel Industry

Abstract: Apparel manufacturing is an industry with high energy consumption and carbon emissions. With the development of the low-carbon economy, low-carbon production in the apparel manufacturing industry become more and more imperative. The apparel industry is encountering great challenges in reducing carbon emissions. Garment sewing comprises a large number of processes, machines and operators. However, the existing studies lack quantitative analysis of carbon sources in the sewing process. This study analyzed the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
(40 reference statements)
0
10
0
Order By: Relevance
“…Studies focused on particular factories, brands or garments also found similar results. For example, a 2019 study of a sewing assembly line for men's shirts in China found that fabrics are the main source of carbon emissions (Zhang and Chen 2019). Another study from China on the impacts of a cotton T shirt production also found that the largest contributors to carbon emissions in the life cycle was the dyeing process (35 per cent); however, this study also found significant emissions in the garment assembly stage (32 per cent) (Zhang et al 2015).…”
Section: Figure 1 Comparison Of the Distribution Of Emissions In The ...mentioning
confidence: 70%
See 1 more Smart Citation
“…Studies focused on particular factories, brands or garments also found similar results. For example, a 2019 study of a sewing assembly line for men's shirts in China found that fabrics are the main source of carbon emissions (Zhang and Chen 2019). Another study from China on the impacts of a cotton T shirt production also found that the largest contributors to carbon emissions in the life cycle was the dyeing process (35 per cent); however, this study also found significant emissions in the garment assembly stage (32 per cent) (Zhang et al 2015).…”
Section: Figure 1 Comparison Of the Distribution Of Emissions In The ...mentioning
confidence: 70%
“…In China, the largest global producer of textiles and garments, the apparel industry is the sixth-largest industry sector in terms of energy consumption (Zhang and Chen 2019). In Bangladesh, the textile and garments industry is the top export earner, generating 81 per cent of gross domestic income.…”
Section: Emissions From Productionmentioning
confidence: 99%
“…39 The applied line balancing problems in garment manufacturing evolved because garment assembly line poses unique balancing problems to those of large body assembly lines such as trucks, buses, aircraft, and machines. 40,41 In most studies, garment assembly line balancing has been implemented using several techniques including ranked positional weight, 42 COMSOAL, 43 largest candidate rule, 44 and simulation. 41 As the complexity of garment assembly line increases depending on the fashion styles, most of these methods become less effective and inferior for line balancing .…”
Section: Assembly Line Balancingmentioning
confidence: 99%
“…The NYTIL trouser assembly line right hip pocket (20)(21)(22)(23)(24), knee pocket preparation (KPP) for making both left and right knee pocket (32)(33)(34)(35)(36), knee flap preparation (KFP) for making both left and right knee flap (38)(39)(40)(41)(42), big loop preparation (BLP) for making seven big loops per trouser (47)(48)(49)(50)(51), small loop preparation (SLP) for stitching small loops and cutting into seven pieces required per trouser (52), adjustable rope preparation (ARP) for cutting and attaching two sets of adjustable rope at two positions on trouser waist band (65)(66), and main body assembly (MBA) for assembling all the prepared parts and other parts (do not require preparation) to the trouser body and involves other operations such as trimming, turning, quality checking, and…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation